ANALISA KELAYAKAN PEMBANGUNAN JALAN TOL PEMALANG BATANG - Ardina Rahmalia; Fahmi Akmal Hasani; Djoko Purwanto; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Pemalang – Batang Toll Road construction has been delayed due to land acquisition problems. It would require second feasibility analysis to the present conditions. Methodologies used include : performance evaluation of Pantura using MKJI 1997, analysis of traffic diverted to the toll road using diversion curve, economic feasibility in term of VOC saving, time saving and cost of accident saving; financial feasibility in term of NPV, BCR, IRR, payback period and NPV=0; and sensitivity analysis in term of reduction income, interest rate changes in toll rates, early year income and increase in investment cost. Pemalang – Batang Toll Road economically feasible. VOC saving for category I Rp 23,49; category IIA Rp 39.237,66 and category IIB Rp 52.518,90. Time saving for category I 27.98 minutes, category IIA 45.745 minutes, and category IIB 63.02 minutes. Accident cost can be saved Rp 43.363.019,00/year/km. Pemalang – Batang Toll Road also financially feasible with NPV= Rp 4.301.297.387.339,00; BCR= 1.787; IRR= 23.226%; payback period occurred in 8 years 7 months 16 days and NPV=0 occurred in 13 years 7 months 23 days. Results of sensitivity analysis are reduction income at least 44.032%; early year income in 21 years and the increase in investment cost amounted to 78.763%. Changes interest rate in toll rates did not affect the financial feasibility.